A study on highly-loaded contacts under dry lubrication for gear applications. (December 2018) - Yilmaz, M.; Kratzer, D.; Lohner, T.; Michaelis, K.; Stahl, K.
Abstract: Highly-loaded contacts in gearboxes are usually lubricated by oil or grease in order to reduce friction and wear and to dissipate heat. Eliminating the fluid lubricant would reduce the no-load losses of gearboxes significantly and omit the use of expensive seals. Surface coatings have strong potential to improve the wear resistance in tribological contacts under dry lubrication, combined with low friction properties. The aim of this study is to investigate highly-loaded uncoated and coated contacts under dry lubrication for gear applications. Case-carburized steel 16MnCr5 was considered as substrate material. Uncoated, tetrahedral amorphous carbon (ta-C) coated and molybdenum disulphide (MoS2 ) coated surfaces were investigated experimentally at a twin-disk test rig and theoretically by means of tribosimulations. All experimental investigations were accompanied by friction and temperature measurements as well as by surface photos and roughness measurements. The experimental results show that under dry lubrication coated contacts can have significant improved tribological performance compared to uncoated contacts. However, the tribological performance is not comparable with highly-loaded lubricated contacts. The theoretical results based on a parametric study show that the thermal conductivity and the modulus of elasticity of the coating have the strongest effect on the contact temperature and the von Mises stress distribution, respectively. Highlights: Moderately-to highly-loaded contacts were investigated under dry lubrication. Rolling-sliding contact conditions were chosen close to gear applications. Reliable operation of uncoated steel contacts was not possible. Coatings can increase the tribological performance up to a certain degree. Influence of physical coating properties were studied by tribosimulations.